1966
DOI: 10.2172/4525075
|View full text |Cite
|
Sign up to set email alerts
|

Orgdp Fuel Reprocessing Studies Summary Progress Report, July Through December, 1965

Abstract: As used 1n the above, "person octmg on behalf of the Commission" includes any employee or J contractor of the Comm1SS1on, or employee of such contractor, to the extent that such employee or contractor of the Commission, or employee of such contractor prepares, d1ssem1notes, or provides access to, any information pursuant to h1s employment or contract w1th the Commission, or h1s employment w1th such contractor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1968
1968
1968
1968

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The average retention for the runs with 4.4-kg UO2 charges was 0.214 kg of UF6 per kg of NaF. This value agrees quite well with data obtained on trapping 54 UF.6 from a fluorine-nitrogen stream in prototype equipment at ORGDP. As shown by Table XXIII, the total uranium accounted for was 100 + 5% of that charged (5% is the estimated analysis accuracy) for seven of the ten runs made.…”
Section: Appendix G Uranium Retention In Trapssupporting
confidence: 86%
“…The average retention for the runs with 4.4-kg UO2 charges was 0.214 kg of UF6 per kg of NaF. This value agrees quite well with data obtained on trapping 54 UF.6 from a fluorine-nitrogen stream in prototype equipment at ORGDP. As shown by Table XXIII, the total uranium accounted for was 100 + 5% of that charged (5% is the estimated analysis accuracy) for seven of the ten runs made.…”
Section: Appendix G Uranium Retention In Trapssupporting
confidence: 86%
“…Gas sorption with tellurium hexafluoride on various + sorbents was studied, both in static and flowing type systems, 1,3 4 to evaluate 13 sorbents as potential trapping agents for tellurium hexafluoride. Radio-·tagged tellurium hexafluoride was used .in the gas-flow studies, These studies revealed that activated alumina can effectively remove tellurium hexafluoride from an off-gas stream containing fluorind.…”
mentioning
confidence: 99%